Diversion of Juvenile Offenders through Community-Based Collaboration - Ramdhan, Salsabila; Pohan, Agustinus (Al Huwiyah: Journal of Woman and Children Studies, 2025)
The protection of children who are facing the law is the responsibility of the law enforcement agencies such as polices,prosecutors and judges. To protect children from the the formal proceedings of the criminal justice system, alternativesettlement of other cases is applied through the diversion process. This study aims to analyze the effectiveness of diversion implementation in handling children in conflict with the law through community involvement. The research method used is juridical-sociological with a qualitative approach, involving interviews and document studies with law enforcement officers and the community in Bandung. The results indicate that the implementation of diversion still faces various obstacles. These include the community’s limited understanding of diversion mechanisms, lack of socialization from law enforcement, and the individualistic character of urban society. Specifically in Bandung City, various obstacles and challenges are still found, both from the side of law enforcement officers and other supports such as the citizen. Strengthening regulations, increasing public education, and enhancing synergy between law enforcement and the community are essential to optimize child protection through diversion. This study recommends ongoing evaluation and reinforcement of community roles at every stage of diversion to achieve the goals of restorative justice effectively. Keywords: Children, Diversion, Juvenile.